Bilateral Spontaneous Pneumothorax in a COVID-19 and HIV-Positive Patient: A Case Report - Cho, Young Min; Guevara, Sara; Aronsohn, Judith; Mumford, James M.; Shore-Lesserson, Linda; Miyara, Santiago J.; Herrera, Martin; Kirsch, Claudia; Metz, Christine N.; Zafeiropoulos, Stefanos; Giannis, Dimitrios; McCann-Molmenti, Alexia; et al. (Frontiers in Medicine, 2021)
This case report describes a 60 year-old Black-American male with a past medical history of human immunodeficiency virus (HIV) infection and hyperthyroidism, who suffered a bilateral spontaneous pneumothorax (SP) in the setting of coronavirus disease 2019 (COVID-19) pneumonia. SP is a well-established complication in HIV-positive patients and only recently has been associated with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection. While HIV and COVID-19 infections have been independently linked with increased risk of SP development, it is unknown if both infections interact in a synergistic fashion to exacerbate SP risk. According to the Centers for Disease Control and Prevention (CDC), patients living with HIV have a higher risk of developing severe COVID-19 infection and the mechanism remains to be elucidated. To the best of our knowledge, this is the first report of a HIV-positive patient, who in the setting of SARS-CoV-2 infection, developed bilateral apical spontaneous pneumothorax and was later found to have a left lower lobe tension pneumothorax. This case highlights the importance of considering SP on the differential diagnosis when HIV-positive patients suddenly develop respiratory distress in the setting of SARS-CoV-2 infection.